1991
DOI: 10.1111/j.1574-6968.1991.tb04732.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of phospholipid and chloroform fumigation analyses for biomass in soil: potentials and limitations

Abstract: A sensitive method for estimating living biomass, based on a direct extraction of phospholipids, was applied to soil. The variation between replicate soil samples was generally below 10%. Recovery from soil was qualitative. Estimates of biomass from the phospholipid assay were not correlated with estimates from the chloroform fumigation‐incubation method (CFIM). In non‐fumigated soil a significant reduction (25–57%) of biomass, as determined from phospholipid analysis, was observed during the 10‐day incubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 22 publications
1
2
1
Order By: Relevance
“…However, no significant ( P > 0.05) difference in the size of the microbial biomass was observed between the control samples and the treated soil for either time period. This level of biomass was similar to the level obtained in other labs ( , ) for fresh samples, and declines in biomass size for controls during laboratory incubations at 25 °C have been reported by others ( , ).…”
Section: Resultssupporting
confidence: 91%
“…However, no significant ( P > 0.05) difference in the size of the microbial biomass was observed between the control samples and the treated soil for either time period. This level of biomass was similar to the level obtained in other labs ( , ) for fresh samples, and declines in biomass size for controls during laboratory incubations at 25 °C have been reported by others ( , ).…”
Section: Resultssupporting
confidence: 91%
“…This is contrary to most earlier studies, which have reported the phospholipid method to give the higher estimate (Balkwill et al, 1989;; see also Peterson et al, 1991). As phospholipids are rapidly degraded in aquatic esosystems, only living cells would be enumerated with the PLFA approach (Vestral& .…”
Section: Discussioncontrasting
confidence: 52%
“…The varying lability of individual lipids, in addition to varying residence times of IPLs driven by particle fluxes, influence the relative contribution of IPLs potentially exported to underlying depths. While IPLs are often considered to hydrolyze quickly after cell death (White et al, 1979;Petersen et al, 1991), it has been demonstrated that certain compounds can remain intact for weeks to months (Harvey et al, 1986;Brandsma, 2011;Logemann et al, 2011). Slower degradation rates were found to be most pronounced in SQDGs (Brandsma, 2011) suggesting a higher potential of this lipid class to survive export to the deep ocean.…”
Section: Utility Of Ipls As Biomarkers For In Situ Planktonic/microbimentioning
confidence: 99%
“…The great chemical diversity of cell membrane intact polar lipids (IPLs) provides some phylogenetic specificity, which has been exploited in the mapping of planktonic and microbial communities in marine environments (Wakeham et al, 2007;Popendorf et al, 2011;Brandsma et al, 2012;Rush et al, 2012;Sollai et al, 2015). Given the susceptibility of their polar head groups to hydrolysis after cell death (White et al, 1979;Harvey et al, 1986;Petersen et al, 1991), the abundance of environmental IPLs is commonly interpreted to represent the occurrence of living cells, and is thus used to determine the in situ abundances of different metabolic and biosynthetic pathways (e.g., Schubotz et al, 2009;Van Mooy and Fredricks, 2010;Wakeham et al, 2012;Schubotz et al, 2018). While the stability of polar head groups has been questioned in sediments (Schouten et al, 2010;Logemann et al, 2011), the short residence time of particles in water column samples (Moran and Buesseler, 1992) allows the use of IPLs to study microbial abundances and contribution to carbon stocks in suspended particles.…”
Section: Introductionmentioning
confidence: 99%